2022
DOI: 10.3390/toxins15010001
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Antivenoms Exert Broad Paraspecific Immunological Binding and In Vitro Inhibition of Medically Important Bothrops Pit Viper Venoms

Abstract: Snakebite envenoming is a life threatening neglected tropical disease that represents a considerable public health concern in the tropics. Viperid snakes of the genus Bothrops are among those of greatest medical importance in Latin America, and they frequently cause severe systemic haemotoxicity and local tissue destructive effects in human victims. Although snakebite antivenoms can be effective therapeutics, their efficacy is undermined by venom toxin variation among snake species. In this study we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Third-generation antivenomics analysis has further proven Bothrofav’s high neutralizing efficacy of all the major immunogenic protein components of B. lanceolatus venom (i.e., metalloproteinases, phospholipases A 2 , serine proteinases, C-type lectin-like proteins, and disintegrins), with the exception of poor immunogenic peptides [ 63 ]. In our study, the Bothrovav-induced prevention of the inhibitory effects of B. lanceolatus venom on vWF collagen type I and type III binding may be related to the reported beneficial effects of the antivenom on coagulopathic activities [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 84%
“…Third-generation antivenomics analysis has further proven Bothrofav’s high neutralizing efficacy of all the major immunogenic protein components of B. lanceolatus venom (i.e., metalloproteinases, phospholipases A 2 , serine proteinases, C-type lectin-like proteins, and disintegrins), with the exception of poor immunogenic peptides [ 63 ]. In our study, the Bothrovav-induced prevention of the inhibitory effects of B. lanceolatus venom on vWF collagen type I and type III binding may be related to the reported beneficial effects of the antivenom on coagulopathic activities [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 84%
“…Commercial antivenoms may exert broad paraspecific immunological binding and neutralization of medically important snake venoms such as in Bothrops [ 38 ]. Sousa et al [ 39 ] compared the composition and reactivity with multispecific Bothrops antivenom (SAB) of venoms collected from six species of Bothrops , Bothropoides and Rhinocerophis snakes, and found that P-III SVMPs are the most antigenic toxins in the venoms of snakes from the Bothrops complex, while class P-I SVMPs, SVSPs and PLA 2 s reacted with SAB in lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of variation across ELISA plates has been minimized because we implemented measures include maintaining a consistent reaction time and temperature, using identical batch numbers for ELISA plates, employing the same ELISA reader, and ensuring the consistent participation of the same experimenter. (4) As the venom samples from each species are pooled from individual snakes, we refrained from testing differences among treatments using t-tests, ANOVA, or nonparametric statistics, as observed in other studies (such as [ 29 , 30 , 38 , 42 , 43 , 45 , 46 ]). For future studies, venom samples from different individuals, populations, or geographical areas can be employed and compared in relevant experiments to enable statistical testing among treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, hibernation, the recency of last venom extraction, and temperature participate in the great variability in venom composition within a population [ 25 , 26 , 27 , 28 ]. Consequently, for human envenoming, venom variation may result in significant differences in symptoms arising from snake bites and innate mechanisms initiating inflammatory reactions critical to host protection and can also undermine the efficacy of the antivenom, which may have a reduced potential to neutralize such a variety of different toxins [ 29 , 30 , 31 ]. Although venom variation and the host response might have been different during the two periods of Bothrofav use, it is very unlikely that these changes explain the periods free of complications following Bothrofav’s initial production and renewal.…”
Section: Discussionmentioning
confidence: 99%